How Sustainable Finance Drives Financial Performance: Evidence from KKUB Firms with 2024 Sustainability Ratings - Pasaribu, Evana; Tambunan, Martua E. (Taxation and Public Finance, 2025)
This study examines the influence of Sustainable Finance (SF) practices on the financial performance of companies operating in Indonesia’s NDC priority sectors by integrating evidence from 2024 sustainability ratings, global GRI-based benchmarks, and regulatory requirements under POJK 51/2017. The research analyzes how ESG integration, sustainability reporting quality, and adherence to the Indonesian Green Taxonomy shape firms’ operational efficiency and financial outcomes, particularly among companies classified as Sustainable Business Activities (KKUB). The originality of this study lies in its cross-sector comparative approach, which links SF implementation to measurable financial results while incorporating updated regional and global sustainability rating frameworks. Findings show that firms with mature ESG governance achieve stronger cost efficiency, improved risk mitigation, and enhanced access to green financing, leading to better overall financial resilience. The results also highlight the role of transparent sustainability reporting in strengthening corporate accountability, aligning environmental disclosures with emerging tax governance expectations, and reducing compliance risks related to emissions and resource use. These insights confirm that integrating SF and high-quality ESG disclosure contributes to long-term firm value while supporting national low-carbon development objectives. The study provides implications for managers, investors, and regulators in optimizing sustainability-driven financial strategies